MELATONIN REDUCES LIPOPOLYSACCHARIDE-INDUCED KIDNEY DAMAGE IN RATS - Sokolović, Danka; Lazarević, Milan; Milić, Dragan; Stanojković , Zoran; Petković, Milan; Stojanović, Nikola; Sokolovic, Dusan (Acta medicae Medianae, 2023)
Lipopolysaccharide (LPS) is a constituent of Gram-negative bacterial cell walls, thus LPS injection has been widely used as a model of experimental acute kidney injury associated with sepsis. LPS-induced sepsis is caused by excessive secretion of pro-inflammatory mediators and reactive oxygen species (ROS). The neurohormone melatonin, which is mainly secreted by the pineal gland, regulates the circadian rhythm, has an anti-inflammatory and immunoregulatory role. Melatonin and its metabolites have been shown to scavenge various free radicals and reactive oxygen intermediates. The aim of this study was to evaluate the effect of melatonin in preventing endotoxemia-induced kidney damage caused by LPS, by analysing the concentration of urea and creatinine in the blood serum of rats. Twenty-eight Wistar albino rats were randomly divided into four groups (n = 7 per group) as follows: 1) Control group, 2) MLT group (50 mg/kg, per os), 3) LPS group (10 mg/kg, i.p.) and 4) LPS + MLT group (10 mg/kg + 50 mg/kg). Serum levels of creatinine and urea were significantly higher (p
Keywords: melatonin, lipopolysaccharide, kidney, urea, creatinine